Inside the spiral: Hostile media, minority perception, and willingness to speak out on a weblog. (September 2016) - Yun, Gi Woong; Park, Sung-Yeon; Lee, Sooyoung
Abstract: This study took a snapshot at the psychological process of spiral of silence in an online environment with South Korean college students as the study participants. In an experiment, a Weblog-embedded news article from a media source incongruent with one's political orientation, as opposed to the same article from a congruent media source, triggered hostile media perception, which in turn led to presumed influence of the online news article on others. The presumed influence on others became a basis for assessing the online climate of opinion and led people to view themselves as a minority against the online climate of opinion. The media source factor, in conjunction with user comments factor, also generated different levels of minority perception both online and in the general society. In contrast to the notion of spiral of silence, minority perception against the general society's climate of opinion increased rather than decreased willingness to speak out. Highlights: Spiral of silence theory was delineated under media perception and presumed media influence. The presumed media influence on others became a basis for assessing the online climate of opinion. Disagreeable user comments with hostile media source generated high minority perception online. Agreeable user comments with hostile media source generated low minority perception in society. Minority perception against the climate of opinion increased willingness to speak out online.